EXPERIENCE OF CYBERBULLYING AND PRACTICES TO COPE WITH IT AMONG HIGHSCHOOL STUDENTS IN HANOI (Proceedings of the Global Public Health Conference, 2025)
This cross-sectional study investigated the prevalence, types, and coping strategiesassociated with cyberbullying among adolescents in Hanoi, Vietnam. This demographic isparticularly vulnerable as Vietnamese adolescents lack access to adequate supportresources. Using respondent-driven sampling to provide a safe and confidential platformfor discussing a sensitive topic, data was collected through self- administered onlinesurveys based on the cyberbullying measurement scale and coping strategy frameworkdeveloped by Patchin and Hinduja. A total of 253 students aged 13–18 from public schoolsparticipated in the study. Results revealed that 51.4% of participants had experienced atleast one of six forms of cyberbullying, and 77.9% had witnessed others beingcyberbullied. These behaviors often led to emotional distress among victims, emphasizingthe significant psychological impact of cyberbullying on adolescents. Additionally, thestudy explored coping strategies and found that students frequently lacked effectivemechanisms to address cyberbullying incidents. The most common response was seekingadvice from friends, reported by 40.7% of participants, while fewer students turned toparents, teachers, or professional support systems for help. This limited reliance on adultsor institutional resources highlights a potential gap in support systems available to studentsin the effectiveness or accessibility of current support systems. These findings underscorethe urgent need for comprehensive educational interventions aimed at raising awarenessabout cyberbullying and equipping students with practical tools to manage and respond tosuch incidents effectively. Schools and policymakers should prioritize the development ofprograms that foster digital resilience, enhance peer support networks, and encourage theinvolvement of trusted adults to create a safer online environment for adolescents.Initiatives like peer mentoring programs can empower adolescents to support one another,fostering a safer and more connected online environment.
Keywords: cyberbullying; coping skills; public health; school and student health